The sources of the evolution of China's provincial economic gap: A green economic growth accounting perspective - Wenju Yang; Ruiyun Long (Kiel Institute for the World Economy (IfW), 2020)
The inter-provincial economic gap in China is obvious and tends to expand, although it is still unclear why this occurs. This paper combines DEA-based green economic growth accounting, growth convergence test and distribution dynamic analysis to show that China's inter-provincial labor productivity demonstrated significant growth convergence between 1997 and 2016, while it was significantly promoted by capital deepening and obviously inhibited by technological progress and human capital accumulation, and the effect of technological efficiency change remained unclear. In addition, the gap of labor productivity level in China's provinces widened significantly, which can be largely attributed to the combined effects of technological progress and capital deepening. The economic growth accounting analysis ignoring Energy and environmental factors tends to overestimate the relative contribution of factor accumulation and underestimate that of TFP changes, while ignoring human capital will lead to opposite biased results, but both of which do not change the qualitative conclusions mentioned above.
Keywords: O18; O47; R11; 330; counterfactual analysis; distribution dynamic analysis; green economic growth accounting; multimodal test; non-parametric test